The "anaerobic threshold" concept is valid in physiology and medicine - Rossiter, H. B. (Medicine & Science in Sports & Exercise, 2021)
In their seminal 1964 paper Wassenman and Mellroy described how the "threshold of anaerobic metabolism in heart failure patients could be detected not only measurements of lactate or pH in arterial blood but also in pulmonary gas exchange. They placed their findings within the context of the pioneering work of Harrison and Pilcher (2) three decades earlier, who identified excessive CO2 output (VCO2) immediately after exercise in heart failure patents compared with controls. It was proposed that the "excess CO2" could not be a product of aerobic metabolism but must be released from bicarbonate when acids are buffered that were formed by anaerobic glycolysis during exercise (Fig. I). The term coined for this concept, "the anaerobic threshold", has been described as both a" milestone" and a "millstone" in exercise physiology (3). Asked by his mentor Julius Comroe how he might advance detection of heart discase, Wasserman proposed that an evaluation might be best done during exercise, when the heart was being stressed. An early sign of heart failure, he proposed, would be reflected in reduced ability for O2 delivery necessary to meet the exercise-induced increase in cellular demand. Because the muscle O2 requirement would be markedly increased by the exercise any failure of O2 transport to meet this demand would result in a metabolic acidosis (via the pasteur effect). Thus, the context for the anaerobic threshold concept is framework that linked inadequate O2 delivery to metabolic acidosis and excess CO2 output. In this contrasting perspective, I argue for the validity of this concept during exercise based on three key observations: